Clinical comparison of fiber-reinforced composite and stainless steel wire for splinting periodontally treated mobile teeth - Akcalı, Aliye; Gümüş, Pınar; Özcan, Mutlu (Brazilian Dental Science, 2014)
Objective: This clinical study evaluated the success of two different splint materials bonded on periodontally treated mobile teeth. Methods: A total of 14 patients were included in the study. Patients were randomly assigned to the groups to receive either with or wire composite splint (WCS) or fiber-reinforced composite splint (FCS). Clinical periodontal parameters were performed and periotest values were recorded at baseline, and after 6 and 12 months. Patients were asked to complete a self-administered questionnaire after the splinting procedures. Failure types for the splints were categorized. Results: Baseline PI values showed significant decrease at 6 month follow up in the WCS (p=0.0019) and FCS (p<0.0001) groups and remained stable after 12 months (WCS; p=0.36, FCS; p=0.63). During the course of the study, PD and RD values exhibited no change between and within groups. Clinical parameters including PD, RD, PI and BOP were stable at 6 and 12 months follow-up period. In 6 patients (4 FCS, 2 WCS), reparable failures occurred during the observation period. In four patients (3 FCS, 1 WCS) splints failed completely and were removed. The periotest values of the failing teeth ranged between 47.3 and 50. In 3 patients in the WCS and 1 patient in the FCS group, periotest values were ? 40 but no splint failures were observed. Conclusion: FCS tends to show increased mechanical limitations compared to WCS. Teeth with periotest values above 40 may be more prone to splint failures independent of the splint material.